Transforming Enterprise Integration: Event-Driven Architecture with AI-Powered Event Processing - Ramadevi Sannapureddy (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Event-Driven Architecture (EDA) with AI-powered event processing represents a transformative paradigm in enterprise integration, enabling organizations to process and respond to business events in real-time rather than relying on traditional batch processing methods. This integration approach leverages artificial intelligence capabilities including Complex Event Processing, Reinforcement Learning, and Natural Language Processing to detect patterns, optimize event routing, and extract meaning from unstructured data. The combination of EDA with cloud-native technologies such as serverless computing and event mesh platforms delivers remarkable performance improvements, including significant reductions in integration latency, substantial increases in processing throughput, and enhanced operational efficiency. Despite implementation challenges related to event schema evolution, latency management, and training data acquisition, organizations implementing these architectures achieve comprehensive benefits through AI-based solutions. As adoption continues to accelerate, emerging capabilities including federated learning, explainable AI, self-healing event networks, and edge-based intelligence promise to further revolutionize enterprise integration approaches, providing foundations for rapid, intelligent responsiveness to changing business conditions.